Integrating in vitro and in silico approaches for exploring antidiabetic potential of dimethyl and thiomethyl indolinone derivatives. - Kashif Ali; Ahmed A Elhenawy; Waqas Alam; Khalaf F Alsharif; Khalid J Alzahrani; Haroon Khan; Long Chiau Ming; Rahul G Ingle (PLoS ONE)
Diabetes mellitus (DM) is a metabolic disorder caused by insulin deficiency. It is a rapidly growing problem with immense social, economic and health related problems. The market available drugs for the management of DM possess several limitations and therefore the discovery of more effective agents is the need of time. The current study was designed to evaluate two oxindole derivatives: (E)-3-(2,4-Dimethylbenzylidene)-6-chloroindolin-2-one (compound 1), and (E)-3-(4-(Methylthio) benzylidene)-6-chloroindolin-2-one (compound 2) against α-amylase, protein glycation, and DPP-IV. In case of in vitro antidiabetic activities, compound 1 demonstrated significant inhibition at various concentrations with IC50 value of 32.917 µg/mL against α-amylase, 210.592 µg/mL against protein glycation and 31.28 µg/mL against DPP-IV. Similarly, when tested at various concentrations, compound 2 illustrated marked inhibition with IC50 value of 42.691 µg/mL on α- amylase, 341.551 µg/mL on protein glycation and 47.192 µg/mL against DPP-IV. Molecular docking studies identified the binding patterns of oxindoles in the active site of targeted protein and enzymes. Moreover, the docking analysis also showed the potent interaction of test compounds with the target sites against α-amylase, protein glycation and DPP-IV. In conclusion, both the compounds are significant inhibitors of α-amylase, protein glycation and DPP-IV in vitro assays with the support of molecular dynamic studies and therefore are potential candidates for further studies.